Closure of the uterine incision with one or two layers after caesarean section: a randomized controlled study in sheep*. (April 2014) - Lapointe-Milot, Korine; Rizcallah, Edmond; Takser, Larissa; Abdelouahab, Nadia; Duvareille, Charles; Pasquier, Jean-Charles
Abstract Objective: To compare the quality of the uterine scar with one or two layer closure after caesarean section by studying biomechanical and pathological properties of the scar. Methods: A randomized controlled trial performed on eight term pregnant ewes assigned into two groups during caesarean according to type of uterine closure: single-layer or double-layer. Hysterectomy was performed 8 months after caesarean delivery. Tensile strength of all scars and of unscarred myometrium was measured. Pathological properties of the scars were analyzed histologically. Results: The force required to reach the yield point was similar between scarred and unscarred myometrium (p = 0.96), and between the scars in single-layer and double-layer closure groups (p = 0.65). There was a significant increase in fibrosis width on the superficial part of the uterus in the double-layer closure group compared to the single-layer group (p = 0.02). Conclusions: Double-layer uterine closure modified wound healing without significant change in biomechanical properties.